A multivariate test against spurious long memory - Philipp Sibbertsen; Christian Leschinski; Marie Holzhausen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
This paper provides a multivariate score-type test to distinguish between true and spurious long memory. The test is based on the weighted sum of the partial derivatives of the multivariate local Whittle likelihood function. This approach takes phase shifts in the multivariate spectrum into account. The resulting pivotal limiting distribution is independent of the dimension of the process, which makes it easy to apply in practice. We prove the consistency of our test against the alternative of random level shifts or monotonic trends. A Monte Carlo analysis shows good finite sample properties of the test in terms of size and power. Additionally, we apply our test to the log-absolute returns of the S&P 500, DAX, FTSE, and the NIKKEI. The multivariate test gives formal evidence that these series are contaminated by level shifts.
Keywords: C12; C32; 330; Multivariate Long Memory; Semiparametric Estimation; Spurious Long Memory; Volatility